Bariatric surgery drives major rearrangements of the intestinal microbiota including the biofilm composition. - Campisciano, Giuseppina; Cason, Carolina; Palmisano, Silvia; Giuricin, Michela; Rizzardi, Alessia; Croce, Lory Saveria; De Manzini, Nicolo; Comar, Manola (Front Biosci (Elite Ed), 2018)
The intestinal microbiota disequilibrium has been associated with obesity, while the role of the gut mucosal biofilms in this pathology is still unknown. We analysed the changes in the intestinal microbiota of obese patients after bariatric surgery with the aim of disclosing the rearrangement of the biofilm configuration. Although the bariatric surgery drives major rearrangements of the gut microbiota, obese patients maintain the enterotype before and after surgery, as shown by normal weight patients, with an increase of and . The enterotype guarantees the strong ability to form a biofilm which allows a more efficient digestion of polysaccharides than planktonic communities and leads to the production of acetate which is a key player to inhibit enteropathogens. Additionally, the laparoscopic gastric bypass induces an increase of , a facultative anaerobic bacterium involved in intestinal and inflammatory disorders. Bariatric surgery influences the microbial composition of gut biofilm. Further studies are needed to elucidate the impact of this variation on recovery after surgery and on weight loss.
Keywords: Biofilms; Case-Control Studies; Gastric Bypass; Gastrointestinal Microbiome; Humans; Intestinal Mucosa; Obesity; Prospective Studies

Benign hereditary chorea and deletions outside NKX2-1: What's the role of MBIP? - Invernizzi, Federica; Zorzi, Giovanna; Legati, Andrea; Coppola, Giovanni; d'Adamo, Pio; Nardocci, Nardo; Garavaglia, Barbara; Ghezzi, Daniele (Eur J Med Genet, 2018)
Heterozygous point mutations or deletions of the NKX2-1 gene cause benign hereditary chorea (BHC) or a various combinations of primary hypothyroidism, respiratory distress and neurological disorders. Deletions proximal to, but not encompassing, NKX2-1 have been described in few subjects with brain-lung-thyroid syndrome. We report on a three-generation Italian family, with 6 subjects presenting BHC and harboring a genomic deletion adjacent to NKX2-1 and including the gene MBIP, recently proposed to be relevant for the pathogenesis of brain-lung-thyroid syndrome. We observed a clear reduction of NKX2-1 transcript levels in fibroblasts from our patients compared to controls; this finding suggests that MBIP deletion affects NKX2-1 expression, mimicking haploinsufficiency caused by classical NKX2-1 related mutations.
Keywords: Cells, Cultured; Chorea; Haploinsufficiency; Humans; Intracellular Signaling Peptides and Proteins; Pedigree; Sequence Deletion; Thyroid Nuclear Factor 1

Boy with fish-mouth meatus. - Cortellazzo Wiel, Luisa; Pederiva, Federica; Castagnetti, Marco; Barbi, Egidio; Pennesi, Marco (Arch Dis Child, 2018)

Bilateral Finger Swelling in an Adolescent. - Naviglio, Samuele; Mazzolai, Michele; Ventura, Alessandro (J Pediatr, 2017)

Bipolar Disorder With Psychotic Features and Ocular Toxoplasmosis: A Possible Pathogenetic Role of the Parasite? - Del Grande, Claudia; Contini, Carlo; Schiavi, Elisa; Rutigliano, Grazia; Maritati, Martina; Seraceni, Silva; Pinto, Barbara; Dell'Osso, Liliana; Bruschi, Fabrizio (J Nerv Ment Dis, 2017)
Recent evidence suggests the involvement of Toxoplasma gondii infection in the emergence of psychotic and affective disorders. In this report, we describe the case of a young Brazilian woman affected by recurrent ocular toxoplasmosis and presenting with a manic episode with psychotic features in the context of a diagnosis of Bipolar Disorder (BD), type I. We observed a relationship between ocular manifestations and the clinical course of bipolar illness, confirmed by molecular analyses (nested-PCR), as well as by the high level of T. gondii specific IgG. This case report is the first showing the presence of circulating parasite DNA at the time of occurrence of psychiatric symptoms, thus providing further support for a possible role of the parasite in the pathogenesis of some cases of BD.
Keywords: Adult; Bipolar Disorder; Brazil; Female; Humans; Toxoplasmosis, Ocular; Young Adult

Bolus feeding has no effect on cerebral hemodynamics, irrespective of gestational age. - Bembich, Stefano; Cont, Gabriele; Bua, Jenny; Orlando, Chiara; Di Benedetto, Donatella; Demarini, Sergio (J Matern Fetal Neonatal Med, 2017)
OBJECTIVE: By multichannel near-infrared spectroscopy, we studied if gestational age has any influence on preterm cerebral hemodynamics, during bolus feeding. METHODS: Oxy-haemoglobin (HbO), as cerebral blood flow estimate, and the ratio between HbO and total haemoglobin (HbO/HbTot), as cerebral oxygenation estimate, were assessed in 40 stable premature infants, during a 10 min bolus feeding. RESULTS: We found no effect of any of the gestational ages studied (25-34 weeks) either on cerebral blood flow or on oxygenation, during a bolus feeding procedure. CONCLUSIONS: Bolus feeding appears not to affect cerebral hemodynamics of uncritically preterm infants, irrespective of gestational age.
Keywords: Cerebrovascular Circulation; Enteral Nutrition; Female; Gestational Age; Heart Rate; Humans; Infant, Newborn; Infant, Premature; Intensive Care Units, Neonatal; Male; Oxygen; Oxyhemoglobins; Spectroscopy, Near-Infrared

A boy with fever and arthralgia. - Poropat, Federico; Pastore, Serena; Gesuete, Valentina; Barbi, Egidio (BMJ, 2017)
Keywords: Anti-Bacterial Agents; Anti-Inflammatory Agents, Non-Steroidal; Antibodies, Bacterial; Aortic Valve Insufficiency; Arthralgia; Child; Echocardiography; Echocardiography, Doppler, Color; Fever; Humans; Male; Mitral Valve Insufficiency; Rheumatic Fever; Rheumatic Heart Disease; Streptolysins

Body mass index curves for Italian preterm infants are comparable with American curves for infants born before 34 weeks of gestational age. - Paviotti, Giulia; Monasta, Lorenzo; Ronfani, Luca; Montico, Marcella; Copertino, Marco; De Cunto, Angela; Demarini, Sergio (Acta Paediatr, 2016)
AIM: Body mass index (BMI)-for-age curves have been developed in the USA, but not compared with other populations. This study created gender-specific intrauterine BMI-for-age curves for Italian preterm infants and compared them with the USA version. METHODS: Data on 92 262 newborn infants, born at 26-42 weeks of gestational age in the north-eastern Italian region of Friuli Venezia Giulia between 2005 and 2013, were analysed to create gender-specific BMI-for-age curves. Gender-specific and age-specific BMI Z scores for Italian infants were calculated using the parameters of the USA growth curves and the World Health Organization charts. RESULTS: Gender-specific BMI-for-age at birth curves were developed for premature Italian infants from 26 gestational weeks. The comparison with the USA charts showed no significant difference in BMI percentiles in Italian infants born at ≤33 gestational weeks, but infants born at ≥34 gestational weeks had a significantly higher BMI than the USA population, by 0.2 standard deviations. CONCLUSION: We developed the first European BMI-for-age at birth curves for premature infants. According to our findings, the Italian curves were comparable to the USA curves for the subgroup of infants born at ≤33 gestational weeks, but not ≥34 gestational weeks.

Bedside diagnosis of two major clinical phenotypes of hypertensive disorders of pregnancy. - Ferrazzi, E; Zullino, S; Stampalija, T; Vener, C; Cavoretto, P; Gervasi, M T; Vergani, P; Mecacci, F; Marozio, L; Oggè, G; Algeri, P; Ruffatti, A; et al. (Ultrasound Obstet Gynecol, 2015)
OBJECTIVE: We hypothesized that fetal abdominal circumference (AC) and Uterine Doppler Pulsatility Index (UtA-PI) could select two homogenous subgroups of women affected by hypertensive disorders of pregnancy (HDP), characterized by the coexistence of maternal hypertension with and without IUGR. METHODS: This is a multicentre study that studied cases affected by HDP in whom fetal AC and UtA-PI had been measured at admission to feto Maternal Medicine Units. Maternal characteristics, pregnancy complications and outcome were recorded. These data allowed us to model the characteristics of fetal growth in cases affected by HDP, and to design a composite index for risk factors of maternal metabolic syndrome (rfMMS) and composite index of severity for maternal organ and/or function damage (OFD). RESULTS: Measurements of fetal AC and UtA-PI allowed us to define a group of HDP with AGA fetuses (HDP-AGAf) diagnosed by normal fetal AC and a UtA-PI (#205), and a group of HDP with IUGR fetuses (HDP-IUGR) diagnosed by fetal AC <5(th) centile and UtA-PI >95(th) centile (#124). Curves fitted to birth-weight of the two groups were significantly different, and gestational age at admission for HDP, <34 or ≥34, had no effect on their models. When birth-weight was expressed as standard deviation score (SDS) of local reference charts, the average SDS (±standard error) corresponded to the 6(th) and 48(th) centile respectively. The risk of developing HDP-AGAf was significantly associated with risk factors for maternal metabolic syndrome (OR= 2.79;CI 1.57-4.97), independently of gestational age. The same risk factors yielded a non significant ORs of developing late onset HDP. Women with HDP-IUGR proved to be associated with the worst clinical outcomes. CONCLUSIONS: This study adds genuine new data based on simple prenatal bedside examinations, that might help to differentiate HDP with IUGR, from HDP with AGA fetuses, associated with different fetal growth patterns and different risk factors, not affected by gestational age at onset of the disease.

"Blaschkoid dyspigmentation" in a child: don't forget fibroblast chromosomal analysis. - Gortani, Giulia; Faletra, Flavio; Bruno, Irene; Berti, Irene; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Abnormalities, Multiple; Child, Preschool; Chromosomes; DNA; Female; Fibroblasts; Humans; Phenotype; Pigmentation Disorders

A brain and heart connection: X-linked periventricular heterotopia. - Naviglio, Samuele; Bruno, Irene; Zanus, Caterina; Faletra, Flavio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Adolescent; Brain; Diagnosis, Differential; DNA Mutational Analysis; Epilepsy; Female; Filamins; Humans; Magnetic Resonance Imaging; Mutation; Periventricular Nodular Heterotopia

Brain sparing effect in growth-restricted fetuses is associated with decreased cardiac acceleration and deceleration capacities: a case-control study. - Stampalija, T; Casati, D; Monasta, L; Sassi, R; Rivolta, M W; Muggiasca, M L; Bauer, A; Ferrazzi, E (BJOG, 2015)
OBJECTIVE: Phase rectified signal averaging (PRSA) is a new method of fetal heart rate variability (fHRV) analysis that quantifies the average acceleration (AC) and deceleration capacity (DC) of the heart. The aim of this study was to evaluate AC and DC of fHR [recorded by trans-abdominal fetal electrocardiogram (ta-fECG)] in relation to Doppler velocimetry characteristics of intrauterine growth restriction (IUGR). DESIGN: Prospective case-control study. SETTING: Single third referral centre. POPULATION: IUGR (n = 66) between 25 and 40 gestational weeks and uncomplicated pregnancies (n = 79). METHODS: In IUGR the nearest ta-fECG monitoring to delivery was used for PRSA analysis and Doppler velocimetry parameters obtained within 48 hours. AC and DC were computed at s = T = 9. The relation was evaluated between either AC or DC and Doppler velocimetry parameters adjusting for gestational age at monitoring, as well as the association between either AC or DC and IUGR with or without brain sparing. RESULTS: In IUGRs there was a significant association between either AC and DC and middle cerebral artery pulsatility index (PI; P = 0.01; P = 0.005), but the same was not true for uterine or umbilical artery PI (P > 0.05). Both IUGR fetuses with and without brain sparing had lower AC and DC than controls, but this association was stronger for IUGRs with brain sparing. CONCLUSIONS: Our study observed for the first time that AC and DC at PRSA analysis are associated with middle cerebral artery PI, but not with uterine or umbilical artery PI, and that there is a significant decrease of AC and DC in association with brain sparing in IUGR fetuses from 25 weeks of gestation to term. TWEETABLE ABSTRACT: Brain sparing in IUGR fetuses is associated with decreased acceleration and deceleration capacities of the heart.

Brain-derived neurotrophic factor serum levels in genetically isolated populations: gender-specific association with anxiety disorder subtypes but not with anxiety levels or Val66Met polymorphism. - Carlino, Davide; Francavilla, Ruggiero; Baj, Gabriele; Kulak, Karolina; d'Adamo, Pio; Ulivi, Sheila; Cappellani, Stefania; Gasparini, Paolo; Tongiorgi, Enrico (PeerJ, 2015)
Anxiety disorders (ADs) are disabling chronic disorders with exaggerated behavioral response to threats. This study was aimed at testing the hypothesis that ADs may be associated with reduced neurotrophic activity, particularly of Brain-derived neurotrophic factor (BDNF), and determining possible effects of genetics on serum BDNF concentrations. In 672 adult subjects from six isolated villages in North-Eastern Italy with high inbreeding, we determined serum BDNF levels and identified subjects with different ADs subtypes such as Social and Specific Phobias (PHSOC, PHSP), Generalized Anxiety Disorder (GAD), and Panic Disorder (PAD). Analysis of the population as a whole or individual village showed no significant correlation between serum BDNF levels and Val66Met polymorphism and no association with anxiety levels. Stratification of subjects highlighted a significant decrease in serum BDNF in females with GAD and males with PHSP. This study indicates low heritability and absence of any impact of the Val66Met polymorphism on circulating concentrations of BDNF. Our results show that BDNF is not a general biomarker of anxiety but serum BDNF levels correlate in a gender-specific manner with ADs subtypes.

[Breastfeeding in the first months of life: data from the "Piccolipiù" cohorts]. - Farchi, Sara; Ronfani, Luca (Epidemiol Prev, 2015)

Beta defensin-1 gene polymorphisms and susceptibility to atypical squamous cells of undetermined significance lesions in Italian gynecological patients. - Casalicchio, Giorgia; Freato, Nadia; Maestri, Iva; Comar, Manola; Crovella, Sergio; Segat, Ludovica (J Med Virol, 2014)
The role of the human beta-defensin 1 (hBD-1) in the susceptibility to the onset of the Atypical Squamous Cells of Undetermined Significance (ASCUS) lesion, in the presence or not of HPV infection, is still unknown. In the current study, the three functional single nucleotide polymorphisms (SNPs) -52G > A, -44C > G, and -20G > A at the 5' un-translated region (UTR) of DEFB1 gene, encoding hBD-1, were analyzed in ASCUS lesion gynecological patients and healthy women from the north-east of Italy (Trieste). Cervical samples from 249 European-Caucasian women were collected, screened for HPV and cytologically evaluated; DEFB1 genotyping has been performed by direct sequencing. No significant differences were found for -52G > A, -44C > G, and -20G > A SNPs allele and genotype frequencies between women with and without ASCUS lesions. DEFB1 minor haplotypes were significantly more frequent in ASCUS lesion positive than negative women, associating with an increased risk of this type of lesion. When women were stratified according to HPV infection status, significant differences in the distribution of -52G > A SNP genotype frequencies were found: the presence of the A allele in the homozygous genotype A/A associated with a lower risk of developing ASCUS lesions in HPV negative women. DEFB1 minor haplotypes were also associated with an increased risk of developing ASCUS lesions, being significantly more frequent in HPV negative women with lesions, than without lesions. Although these results highlight the possible involvement of DEFB1, further studies are needed to support the role of DEFB1 in the modulation of the susceptibility to ASCUS lesions.
Keywords: 5' Untranslated Regions; Adolescent; Adult; Atypical Squamous Cells of the Cervix; beta-Defensins; Female; Genotype; Humans; Italy; Papillomavirus Infections; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Uterine Cervical Neoplasms; Young Adult

Block of the mevalonate pathway triggers oxidative and inflammatory molecular mechanisms modulated by exogenous isoprenoid compounds. - Tricarico, Paola Maura; Kleiner, Giulio; Valencic, Erica; Campisciano, Giuseppina; Girardelli, Martina; Crovella, Sergio; Knowles, Alessandra; Marcuzzi, Annalisa (Int J Mol Sci, 2014)
Deregulation of the mevalonate pathway is known to be involved in a number of diseases that exhibit a systemic inflammatory phenotype and often neurological involvements, as seen in patients suffering from a rare disease called mevalonate kinase deficiency (MKD). One of the molecular mechanisms underlying this pathology could depend on the shortage of isoprenoid compounds and the subsequent mitochondrial damage, leading to oxidative stress and pro-inflammatory cytokines' release. Moreover, it has been demonstrated that cellular death results from the balance between apoptosis and pyroptosis, both driven by mitochondrial damage and the molecular platform inflammasome. In order to rescue the deregulated pathway and decrease inflammatory markers, exogenous isoprenoid compounds were administered to a biochemical model of MKD obtained treating a murine monocytic cell line with a compound able to block the mevalonate pathway, plus an inflammatory stimulus. Our results show that isoprenoids acted in different ways, mainly increasing the expression of the evaluated markers [apoptosis, mitochondrial dysfunction, nucleotide-binding oligomerization-domain protein-like receptors 3 (NALP3), cytokines and nitric oxide (NO)]. Our findings confirm the hypothesis that inflammation is triggered, at least partially, by the shortage of isoprenoids. Moreover, although further studies are necessary, the achieved results suggest a possible role for exogenous isoprenoids in the treatment of MKD.
Keywords: Animals; Apoptosis; Carotenoids; Carrier Proteins; Cell Line; Cytokines; Diterpenes; Humans; Mevalonate Kinase Deficiency; Mevalonic Acid; Mice; Mitochondria; Nitric Oxide; Phytol; Terpenes

A boy with sudden headache. - Norbedo, Stefania; Naviglio, Samuele; Murru, Flora Maria; Cavallin, Roberta; Giurici, Nagua; Rabusin, Marco; Barbi, Egidio (Pediatr Emerg Care, 2014)
Headache is a common presenting complaint in pediatric emergency departments. The goal of emergent evaluation is to identify those children with potentially life-threatening conditions. We present the case of an adolescent boy presenting with headache and hypertension who was diagnosed with a catecholamine-secreting abdominal paraganglioma. Genetic testing eventually led to the diagnosis of SDHB-related hereditary paraganglioma-pheochromocytoma syndrome. Alarm features ("red flags") in children presenting with headache are reviewed, as well as the main features of paragangliomas and the indications for genetic testing.
Keywords: Abdominal Neoplasms; Adolescent; Emergencies; Headache; Humans; Male; Paraganglioma

Breastfeeding and migraine drugs. - Davanzo, Riccardo; Bua, Jenny; Paloni, Giulia; Facchina, Giulia (Eur J Clin Pharmacol, 2014)
PURPOSE: Breastfeeding women may suffer from migraine. While we have many drugs for its treatment and prophylaxis, the majority are poorly studied in breastfeeding women. We conducted a review of the most common anti-migraine drugs (AMDs) and we determined their lactation risk. METHODS: For each AMD, we collected all retrievable data from Hale's Medications and Mother Milk (2012), from the LactMed database (2014) of the National Library of Medicine, and from a MedLine Search of relevant studies published in the last 10 years. RESULTS: According to our review, AMDs safe during breastfeeding are as follows: low-dose acetylsalicylic acid (ASA), ibuprofen, sumatriptan, metoprolol, propranolol, verapamil, amitriptyline, escitalopram, paroxetine, sertraline, acetaminophen, caffeine, and metoclopramide. AMDs compatible with breastfeeding but warranting caution are as follows: diclofenac, ketoprofen, naproxen, most new triptans, topiramate, valproate, venlafaxine, and cyproheptadine. Finally, high-dose ASA, atenolol, nadolol, cinnarizine, flunarizine, ergotamine, methysergide, and pizotifen are contraindicated. CONCLUSIONS: According to our review, the majority of the revised AMDs were assessed to be compatible with breastfeeding.
Keywords: Adrenergic beta-Antagonists; Analgesics, Non-Narcotic; Animals; Anti-Inflammatory Agents, Non-Steroidal; Anticonvulsants; Antidepressive Agents; Breast Feeding; Calcium Channel Blockers; Female; Humans; Migraine Disorders; Tryptamines

Breastfeeding during pregnancy: safety and socioeconomic status. - Monasta, Lorenzo; Cetin, Irene; Davanzo, Riccardo (Breastfeed Med, 2014)
Keywords: Breast Feeding; Female; Humans; Lactation; Male; Pregnancy; Pregnancy Complications; Weaning

Breastfeeding and neonatal weight loss in healthy term infants. - Davanzo, Riccardo; Cannioto, Zemira; Ronfani, Luca; Monasta, Lorenzo; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: Neonatal weight loss is universally recognized, yet poorly understood. Limited professional consensus exists on the definition of lower limit of safe weight loss. OBJECTIVE: Our aim was to assess the extent of neonatal weight loss and its association with selected clinical variables in a population of healthy term infants cared for using a specific protocol on weight loss. METHODS: We retrospectively considered 1003 infants consecutively admitted to the regular nursery of the Institute for Maternal and Child Health "Burlo Garofolo" (Trieste, Italy). We studied the relationship of selected variables with neonatal weight loss recorded during the hospital stay. We also analyzed all readmissions in the first month of life as a result of weight loss and its complications. RESULTS: We observed a mean absolute weight loss of 228 g ± 83g, and a mean percent weight loss of 6.7% ± 2.2%. Weight loss ≥ 10% and > 12% were 6% and 0.3%, respectively. In multivariate logistic regression, cesarean section, hot season, any formula feeding, and jaundice not requiring phototherapy were independently associated with neonatal weight loss ≥ 8%. Conversely, low gestational age status was associated with lower weight loss. Readmission within the first month of life because of dehydration occurred in 0.3% of infants. CONCLUSIONS: Breastfeeding, compared to formula feeding, may not be a risk factor for greater early neonatal weight loss, at least in contexts in which weight is routinely monitored, breastfeeding is repeatedly assessed and appropriately supported, and careful supplementation is prescribed to limit and promptly treat excess weight loss and its related complications.
Keywords: Apgar Score; Breast Feeding; Delivery, Obstetric; Gestational Age; Humans; Infant, Newborn; Length of Stay; Patient Readmission; Retrospective Studies; Seasons; Weight Loss

Breastfeeding at NICU discharge: a multicenter Italian study. - Davanzo, Riccardo; Monasta, Lorenzo; Ronfani, Luca; Brovedani, Pierpaolo; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: Human milk is the optimal form of nutrition for infants, especially sick or compromised infants, yet international data suggest that breastfeeding (feeding at the breast) and the use of expressed human milk (mother's and donor's milk) are limited in patients cared for in the neonatal intensive care unit (NICU). OBJECTIVE: The goal of this study was to examine feeding status at hospital discharge among high risk infants. METHODS: We used the 1991 World Health Organization infant feeding definitions, applied to the 72 hour period preceding discharge from the NICU. The study sample consisted of all high risk infants discharged from July 1, 2005, to June 30, 2006 from 13 Italian NICUs. Data on infant feeding in the last 72 hours were collected at discharge from the medical records. RESULTS: We recorded data from 2948 subjects with a median gestational age of 35 weeks (IQR, 32-38), a median birth weight of 2200 g (IQR, 1630-2920) and a median length of stay of 16 days (IQR, 8-33). At discharge, 28% of all infants were fed exclusively with human milk: 31%, 25%, 22% and 33% respectively in the <1500 g, 1500-2000 g, 2000-2499 g and ≥ 2500 g birth weight categories. The proportion of infants not fed with human milk varied from 6 to 82% across different centers. CONCLUSION: Our study found limited breastfeeding and use of human milk among the NICU infants at discharge. At discharge, infants with a birth weight 1500-2499 g were fed exclusively with human milk less than those in higher or lower birth weight categories.
Keywords: Breast Feeding; Humans; Infant, Low Birth Weight; Infant, Newborn; Infant, Premature; Intensive Care Units, Neonatal; Italy; Logistic Models; Multivariate Analysis; Patient Discharge

A boy with acute strabismus. - Poropat, Federico; Ventura, Giovanna; Murru, Flora M; Orzan, Eva; Maschio, Massimo (J Pediatr, 2012)
Keywords: Acute Disease; Child; Humans; Magnetic Resonance Imaging; Male; Mucocele; Strabismus

Burden of disease caused by otitis media: systematic review and global estimates. - Monasta, Lorenzo; Ronfani, Luca; Marchetti, Federico; Montico, Marcella; Vecchi Brumatti, Liza; Bavcar, Alessandro; Grasso, Domenico; Barbiero, Chiara; Tamburlini, Giorgio (PLoS One, 2012)
BACKGROUND: Otitis media (OM) is a leading cause of health care visits and drugs prescription. Its complications and sequelae are important causes of preventable hearing loss, particularly in developing countries. Within the Global Burden of Diseases, Injuries, and Risk Factors Study, for the year 2005 we estimated the incidence of acute OM, chronic suppurative OM, and related hearing loss and mortality for all ages and the 21 WHO regional areas. METHODS: We identified risk factors, complications and sequelae of OM. We carried out an extensive literature review (Medline, Embase, Lilacs and Wholis) which lead to the selection of 114 papers comprising relevant data. Data were available from 15 of the 21 WHO regions. To estimate incidence and prevalence for all countries we adopted a two stage approach based on risk factors formulas and regression modelling. RESULTS: Acute OM incidence rate is 10.85% i.e. 709 million cases each year with 51% of these occurring in under-fives. Chronic suppurative OM incidence rate is 4.76 ‰ i.e. 31 million cases, with 22.6% of cases occurring annually in under-fives. OM-related hearing impairment has a prevalence of 30.82 per ten-thousand. Each year 21 thousand people die due to complications of OM. CONCLUSIONS: Our study is the first attempt to systematically review the available information and provide global estimates for OM and related conditions. The overall burden deriving from AOM, CSOM and their sequelae is considerable, particularly in the first five years of life and in the poorest countries. The findings call for incorporating OM-focused action within preventive and case management strategies, with emphasis on the more affected.
Keywords: Cost of Illness; Hearing Loss; Humans; Internationality; Otitis Media

Breastfeeding to 24 months of age in the northeast of Italy: a cohort study. - Carletti, Claudia; Pani, Paola; Knowles, Alessandra; Monasta, Lorenzo; Montico, Marcella; Cattaneo, Adriano (Breastfeed Med, 2011)
AIM: This study assessed the prevalence and duration of breastfeeding up to 24 months and the associated socioeconomic determinants in a birth cohort of children. METHODS: Four hundred infants born in a hospital in the north east of Italy were enrolled at birth and followed up for 36 months. Data on infant feeding were gathered through a feeding diary compiled at fixed intervals. Data were also gathered on type of delivery and weight, length, and health status at birth, as well as on selected socioeconomic indicators of the mothers. A multivariate logistic regression analysis was used to determine any association that exclusivity and duration of breastfeeding may have with selected socioeconomic variables and with health conditions of the infants at birth. RESULTS: Ninety-eight percent of mothers initiated breastfeeding, 69% of them exclusively. This rate, however, had declined to 6% by 6 months. There was a remarkable endurance of breastfeeding at 24 months (12%). The variables significantly associated with exclusive breastfeeding at 3 months and any form of breastfeeding at 12 months are mother's age (p=0.007 at 3 months, p=0.026 at 12 months) and postdischarge hospital admission (p=0.029 at 3 months). CONCLUSIONS: In this population, breastfeeding rates are higher than previously reported, but lower than recommended, especially as far as exclusivity is concerned. Full implementation of the World Health Organization-UNICEF Baby Friendly Initiatives in hospitals and communities is needed to improve them further. Monitoring systems should include the collection of data on breastfeeding beyond 12 months of age.
Keywords: Adult; Age Factors; Birth Weight; Breast Feeding; Cohort Studies; Family Characteristics; Female; Gestational Age; Guideline Adherence; Health Promotion; Humans; Infant; Infant, Newborn; Italy; Neonatal Screening; Prevalence; Socioeconomic Factors; Time Factors

Beta defensin-1 gene (DEFB1) polymorphisms are not associated with atopic dermatitis in children and adolescents from northeast Brazil (Recife, Pernambuco). - Segat, Ludovica; Guimarães, Rafael L; Brandão, Lucas A C; Rocha, Cintia R C; Zanin, Valentina; Trevisiol, Chiara; de Lima Filho, José Luiz; Crovella, Sergio (Int J Dermatol, 2010)
BACKGROUND: Atopic dermatitis (AD) is a common inflammatory skin disease resulting from the interplay between environmental, immunological and genetic factors. In our study, we investigated the role of three single nucleotide polymorphisms (SNPs) at 5'-UTR of DEFB1 gene, encoding for the human beta defensin-1, on the susceptibility to develop AD in a group of Brazilian children and adolescents. METHODS: Three SNPs, -20 G/A (rs11362), -44 C/G (rs1800972), and -52 G/A (rs1799946) at 5'-UTR of DEFB1 gene were genotyped in two groups of children and adolescents, one affected by AD (96 subjects), the other healthy (191 individuals), from northeast Brazil. RESULTS: -44 C/G frequencies were comparable between the two groups. The -20 GG genotype was more frequent in AD subjects than in healthy controls; the -52 GG, conversely, was more frequent in healthy controls than in AD. However, both these differences did not reach statistical significance. Also, association between SNPs and AD severity has been shown. The analysis of DEFB1 haplotypes did not highlight any association of the three SNPs with AD development or disease severity. CONCLUSIONS: Our results seem to exclude a role for the -44 C/G DEFB1 SNPs on the pathogenesis and severity of AD, while for the -20 C/G and -52 G/A, even if not statistically significant, we evidenced a slight trend for susceptibility (-20 GG) and protection (-52 GG) for the development of AD. However, as controversial findings have been reported in the literature, the role of DEFB1 in the development of AD and in the severity of the phenotype deserves further investigation.
Keywords: Adolescent; beta-Defensins; Brazil; Child; Child, Preschool; Dermatitis, Atopic; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Infant; Male; Polymorphism, Single Nucleotide; Risk Factors